Comparison of progressive collapse resistance of frame with specially shaped columns and frame with rectangular columns - Qingwei Chen; Hailong Zhao; Tiecheng Wang (Tehnički Vjesnik, 2017)
RC frame structures with specially shaped columns and RC frame structures with rectangular columns are different types of structures with different column sections. A progressive collapse analysis model of RC frames was proposed using the beam-column element and joint element based on the program OpenSees. Progressive collapse performance of the experimental frame was simulated and the calculation results were in good agreement with the experimental results. The characteristics of progressive collapse performance of frames with specially shaped columns were studied by comparing the progressive collapse resistance of one frame with specially shaped columns with that of three frames with rectangular columns which were designed in accordance with three different principles. It was observed from the results that the progressive collapse resistance of frame with specially shaped columns and frames with rectangular columns with the same reinforcement under the same seismic fortification, design and application conditions were equivalent. The frame with specially shaped columns had a superior performance to resist progressive collapse.